Guz rzekomy oczodołu w przebiegu choroby Ormonda - Murawska, Joanna; Lipowski, Paweł; Raczyńska, Krystyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Retroperitoneal fibrosis (RPF) is characterized by the presence of a fibro-inflammatory tissue, which usually surrounds the abdominal aorta and the iliac arteries and extends into the retroperitoneum. Up to 15% of patients have additional fibrotic processes outside the retroperitoneum. Retroperitoneal fibrosis is generally idiopathic, but can also be secondary to the use of certain drugs, malignant diseases, infections and surgery. The etiology of idiopathic retroperitoneal fibrosis, so called „Ormond’s disease”, remains unknown. In this study we present the 54 years old woman with orbital pseudotumour of right lacrimal gland associated with retroperitoneal fibrosis. Diagnosis was confirmed with computed tomography of abdominal cavity and orbit. Needle biopsy from the tumour in the orbit revealed only fibrous tissue with signs of chronic inflammation. Together with typical findings of an idiopathic retroperitoneal fibrosis, the final diagnosis of Ormond’s disease with orbital pseudotumorous fibrosis was made. It is important that both, the ophthalmologist and the urologist are aware of the existence of this association, so that suitable treatment can be initiated without delay.